IDENTIFIKASI ATRIBUT KEPUASAN KONSUMEN DAN PELAYANAN RUMAH MAKAN OLAHAN AYAM DI KOTA BANDAR LAMPUNG - Ayu Prasetyowati; Agus Hudoyo; Kordiyana K Rangga (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2016)
The attributes used in the previous studies of the restaurant consumer satisfaction were very varied.  Therefore, this study aims to identify the attributes of the consumer satisfaction and service forthe processed chicken restaurants in Bandar Lampung.  The data was collected in September-October 2015.  The technique used for sampling was accidental sampling in which  data from 60 respondents were the scores for the attributes of satisfaction and service. Moreover, the data were tested by using the validity and reliability tests. The next step is gathering the data of attributes from 60 respondents of two processed chicken restaurants. The analysis methods used were descriptive analysis, validity and reliability test and Importance Performance Analysis (IPA). The research showed that the attributes identified were taste, price, menu diversity, nutrition, suitability menu, consistency of service time, comfort, service speed,hospitality,responsiveness of suggestion, fairness of service,accuracy of writing order, ease of payment, cleanliness of restaurant, waitress’ understanding of the products, cashier thoroughness, completeness of cutlery, location, parking area, security of parking, air conditioning, wastafel, toilet, mosque and entertainment.  The attributes of customer satisfaction and service restaurants that have been identified can be applied processed chicken in the city of Bandar Lampung, but the accuracy attribute accuracy of writing order, park security of parking, wastafel, mosque, and parking area needs to be improved by the restaurant.Key words: attributes, consumer satisfaction,validity and reliabilty test, serviceThe attributes used in the previous studies of the restaurant consumer satisfaction were very varied.  Therefore, this study aims to identify the attributes of the consumer satisfaction and service forthe processed chicken restaurants in Bandar Lampung.  The data was collected in September-October 2015.  The technique used for sampling was accidental sampling in which  data from 60 respondents were the scores for the attributes of satisfaction and service. Moreover, the data were tested by using the validity and reliability tests. The next step is gathering the data of attributes from 60 respondents of two processed chicken restaurants. The analysis methods used were descriptive analysis, validity and reliability test and Importance Performance Analysis (IPA). The research showed that the attributes identified were taste, price, menu diversity, nutrition, suitability menu, consistency of service time, comfort, service speed,hospitality,responsiveness of suggestion, fairness of service,accuracy of writing order, ease of payment, cleanliness of restaurant, waitress’ understanding of the products, cashier thoroughness, completeness of cutlery, location, parking area, security of parking, air conditioning, wastafel, toilet, mosque and entertainment.  The attributes of customer satisfaction and service restaurants that have been identified can be applied processed chicken in the city of Bandar Lampung, but the accuracy attribute accuracy of writing order, park security of parking, wastafel, mosque, and parking area needs to be improved by the restaurant. Key words: attributes, consumer satisfaction,validity and reliabilty test, service